Cordylancistrus santarosensis (Siluriformes: Loricariidae), a new species with unique snout deplatation from the Río Santa Rosa, Ecuador - Tan, Milton; Armbruster, Jonathan W. (Zootaxa, 2012)
Cordylancistrus santarosensis is described based on five specimens from the Río Santa Rosa, Ecuador. This species canbe distinguished from all other members of the Chaetostoma group by having plates on the tip of the snout (except for acentral region at the extreme anterior edge), but lacking plates laterally on the head. This snout plating condition is intermediate between the fully plated snout of other Cordylancistrus and the unplated snout of Chaetostoma.